Anti‐plasticizing Effect of Amorphous Indomethacin Induced by Specific Intermolecular Interactions with PVA Copolymer. Issue 9 (2nd June 2014) - Ueda, Hiroshi; Aikawa, Shohei; Kashima, Yousuke; Kikuchi, Junko; Ida, Yasuo; Tanino, Tadatsugu; Kadota, Kazunori; Tozuka, Yuichi
<x xml:space="preserve">Abstract</x> The mechanism of how poly(vinyl alcohol‐co‐acrylic acid‐co‐methyl methacrylate) (PVA copolymer) stabilizes an amorphous drug was investigated. Solid dispersions of PVA copolymer, poly(vinyl pyrrolidone) (PVP), and poly(vinyl pyrrolidone‐co‐vinyl acetate) (PVPVA) with indomethacin (IMC) were prepared. The glass transition temperature (Tg)‐proportion profiles were evaluated by differential scanning calorimetry (DSC). General Tg profiles decreasing with the IMC ratio were observed for IMC–PVP and IMC–PVPVA samples. An interesting antiplasticizing effect of IMC on PVA copolymer was observed; Tg increased up to 20% IMC ratio. Further addition of IMC caused moderate reduction with positive deviation from theoretical values. Specific hydrophilic and hydrophobic interactions between IMC and PVA copolymer were revealed by infrared spectra. The indole amide of IMC played an important role in hydrogen bonding with PVA copolymer, but not with PVP and PVPVA. X‐ray diffraction findings and the endotherm on DSC profiles suggested that PVA copolymer could form a semicrystalline structure and a possibility of correlation of the crystallographic nature with its low hygroscopicity was suggested. PVA copolymer was able to prevent crystallization of amorphous IMC through both low hygroscopicity and the formation of a specific intermolecular interaction compared with that with PVP and PVPVA. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2829–2838, 2014